Pancasila sebagai Agama Sipil? Analisis Kritis dalam Kerangka Teologi Publik Kristen di Indonesia - Taneo, Rolin Ferdilianto Sandelgus (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
In recent years, there has been a growing movement in Indonesia seeking to reject Pancasila as the state ideology. However, this effort has not gained significant public support. Rejecting Pancasila is equivalent to rejecting Indonesia’s foundational commitment to diversity, a value that has sustained national unity. Although Pancasila is not a religion, its principles are deeply consistent with core teachings found across various religious traditions, making it a unique ideological basis for the Indonesian nation. This study aims to explore whether Pancasila can be understood and accepted as a form of civil religion within Indonesian society. It also seeks to contribute to the development of public theological discourse, particularly from a Christian Protestant perspective, in response to current misunderstandings about Pancasila as civil religion among Christian communities. Employing a qualitative method through a literature study, the analysis draws from theological, philosophical, and socio-political sources. The study concludes that Pancasila, viewed through the lens of public theology, can indeed serve as a civil religion that strengthens national identity without contradicting religious beliefs.